基于矢量环装配模型的二维公差分析 - 彭和平; 刘晓军 (Jixie Chuandong, 2007)
Traditional tolerance analysis methods require an explicit function to describe the relationship between the resultant assembly dimensions and manufactured component dimensions. Such an explicit assembly function may be difficult or impossible to obtain for complex 2-D assemblies. A new method is presented for tolerance analysis of 2-D mechanical assemblies based on vector loop-based models. It has a significant advantage over traditional tolerance analysis methods in that it does not require this explicit assembly function. Furthermore, the tolerance analysis problem of 2-D assemblies can be solved by vector operating to obtain the tolerance sensitivity coefficients. An example is presented to demonstrate the effectiveness of the proposed method.